PERILAKU KEPEMIMPINAN, KETERAMPILAN MANAJERIAL, MANAJEMEN KONFLIK, DAYA TAHAN STRES, DAN KINERJA GURU - Rudolf Kempa (Jurnal Ilmu Pendidikan, 2016)
Leadership, Managerial Skills, Conflict Management, Stress-resilience Capacity, and Teachers' Performance. This article described the correlation between leadership' behavior, managerial skill, management conflict, and durability of teachers' job with teachers'working performance. The population of the study is the state elementary teachers in Ambon, from 142 state elementary schools. Proportional random sampling  technique is used resulted in 332 subjects in this study. In collecting the data, the questionnairre is used as the instrument. Descriptive and Structural Equation Modeling  techniques are applied in analyzing the data. The result of descriptive analysis show that all the variables can be categoreized as good. In general, the result of SEM analysis can be described that there are  the positive and significant correlation between leadership' behavior, managerial skill, management conflict, durability of teachers' job with teachers' working performance at state elemantary teachers in Ambon.